2021
DOI: 10.3390/ijms22073771
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Involved in Fe–S Cluster Biosynthesis of Nitrogenase in Paenibacillus polymyxa WLY78

Abstract: NifS and NifU (encoded by nifS and nifU) are generally dedicated to biogenesis of the nitrogenase Fe–S cluster in diazotrophs. However, nifS and nifU are not found in N2-fixing Paenibacillus strains, and the mechanisms involved in Fe–S cluster biosynthesis of nitrogenase is not clear. Here, we found that the genome of Paenibacillus polymyxa WLY78 contains the complete sufCDSUB operon, a partial sufC2D2B2 operon, a nifS-like gene, two nifU-like genes (nfuA-like and yutI), and two iscS genes. Deletion and comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The mechanisms underlying Fe-S cluster biosynthesis in various bacterial species involved in nitrogenase are still not well understood. In IY22, a fully functional nif operon was not observed; thus, it is likely that the NifS and SufCDB proteins play the role of a specific sulfur donor and molecular scaffold, sequentially, in the assembly of nitrogenase Fe-S clusters, as observed in P. polymyxa WLY78 [ 64 ]. In contrast, the fixABCX operon in IY22 may be associated with nitrogen fixation, as in Azospirillum [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms underlying Fe-S cluster biosynthesis in various bacterial species involved in nitrogenase are still not well understood. In IY22, a fully functional nif operon was not observed; thus, it is likely that the NifS and SufCDB proteins play the role of a specific sulfur donor and molecular scaffold, sequentially, in the assembly of nitrogenase Fe-S clusters, as observed in P. polymyxa WLY78 [ 64 ]. In contrast, the fixABCX operon in IY22 may be associated with nitrogen fixation, as in Azospirillum [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…When inoculated into growth medium, Nguyenibacter sp. L1 secretes significantly higher quantities of gluconic acid relative to other organic acids, thereby aiding the solubilization of Al-P ( Li et al, 2021 ). Gluconic acid, a type of organic acid, assists in transforming the immobilized mineral phosphates (which contain phosphorus) into a form that is readily available for biological uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Within our laboratory, strain L1 has been identified as exhibiting high AlPO4 solubilizing capability and was initially classified as Nguyenibacter based on its 16S rRNA gene sequence ( Li Q. et al, 2021 ). However, given the paucity of genomic information available for this species, a more comprehensive molecular examination of strain L1 is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the nitrogenase activity in the mixture of K. oxytoca Fe and MoFe protein is much higher than that in the mixture of P. sabinae Fe and MoFe (Li et al, 2021a). Recently, we have revealed that the sufCDSUB operon, nifS-like and yutI genes were involved in the Fe-S cluster biosynthesis of nitrogenase in P. polymyxa WLY78 (Li et al, 2021b). In the future, we can co-express nifH and these genes involved in Fe-S cluster biosynthesis of P. polymyxa WLY78 in yeast to investigate whether the Fe activity can be enhanced.…”
Section: Co-expression Of Paenibacillus Polymyxa Nifh and Klebsiella ...mentioning
confidence: 99%